Evaluation Of Port Service User Services At Tanjung Kapal Crossing Port, Bengkalis District, Riau Province - Wijaya, Novan Gunawan; Setiawan, Bambang; Agustini, Elfita; Susanto, Novi Tri; Azzahra, Istiana (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2023)
The Tanjung Kapal Ferry Port serves one route, namely the Rupat – Dumai route. Based on the results of the survey in the field, it was found that several services for service users had not been implemented properly, such as the unavailability of fire extinguishers, evacuation route instructions, evacuation gathering points, first aid equipment, wheelchairs, floor plans/layouts port, passenger baggage, parking attendants, special needs passenger facilities, nursing mother room, signs at the pier, weigh bridge, and arrival and departure schedules at the counter. This research uses the methodPerformance Gap – Importanceto determine the gap between service users' expectations of perceived service quality and quadrant mapping Importance Performance Analysisto find out the attributes that are the main priority for improving service quality. Based on the results of Gap analysisPerformance – Importancea gap was found highest for passenger service at the port with a value of - 2.30 on attribute 32 and attribute. The highest gap for ship service at the port with a value of - 0.66 on attribute 1 and attribute 8. The highest gap for vehicle service at the port with a value of - 2 .10 on attribute.Based on the results of the Quadrant Mapping analysisImportance Performance Analysis There are 10 attributes in quadrant I for passenger services, 2 attributes for ship services and 8 attributes for vehicle services as the main priority for improvement so that the level of service user satisfaction can increase.